Assistive technologies for differently abled students - Dhamdhere, Sangeeta; Andres, Frederic (IGI Global, 2022)
Assistive technologies for differently abled students explores how to implement effective assistive technologies and other related services for providing differently abled students an education that is high quality and equal to their peers, enabling them to go on and excel in their field and obtain employment. Topics that are highlighted within this book include an overview for the different types of diverse assistive technologies for all types of students including students with visual impairments, learning disabilities, physical challenges, and more. This book is ideal for school administrators, researchers of higher educational institutes, non-governmental organizations, assistive technology experts, IT professionals, social workers, inservice and preservice teachers, teacher educators, practitioners, researchers, academicians, and students looking for information on the types of assistive technologies being employed in education for all types of differently abled students